Al-Adillah Al-Mukhtalaf Fiha : Sadd Al-Zari’ah - Muhammad Idris Sarumpaet; Dhiauddin Tanjung (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
The results of this research show that Sadd al-dzari'ah is a method of making legal decisions (istinbath al Hukum) in Islam. Through this method, human efforts are protected and guarded against falling into damage (Mafsadah), by closing and blocking all facilities, tools and wasilah. (intermediary) that will be used to carry out an action. Meanwhile, the opposite of Sadd al-Dzari'ah is Fath Adz-Dzariah, opening (allowing) the use of means, tools and/or wasilah that will be used to carry out an action. The approach the author uses is a descriptive analysis approach. The author describes the opinions of the ulama, the arguments along with several examples of implementation in Islamic muamalah and then analyzes them, so that the author comes to the conclusion that Saddu al-Dzari'ah is a preventive action method used by some ulama in solving the problems of Islamic muamalah.